Wasiat Manis (Warga Siaga Dan Tanggap Kencing Manis) Melalui Penyuluhan Dengan Media Poster Dan Leaflet Untuk Meningkatkan Kepatuhan Berobat Di Puskesmas Ngronggot - Winarti, Eko; Trisnani, Adhe Putri (Jurnal Sains Farmasi Dan Kesehatan, 2026)
Diabetes mellitus is a non-communicable disease that requires long-term management and adherence to treatment to prevent complications. Promotive and preventive efforts through community empowerment are important strategies in controlling diabetes mellitus in primary health care. The WASIAT MANIS (Warga Siaga dan Tanggap Kencing Manis) program was developed as a health promotion innovation through outreach using posters and leaflets. This study aims to analyze the effect of the WASIAT MANIS program on improving adherence to treatment among diabetes mellitus patients at the Ngronggot Community Health Center based on the Health Belief Model theory. The study used a pre-experimental design with a one-group pretest–posttest approach on 30 diabetes mellitus patients selected by purposive sampling. Treatment adherence was measured using questionnaires before and after the intervention. The results showed an increase in the average treatment adherence score from 32.3 before the intervention to 81.3 after the intervention. In addition, there was an increase in visits by diabetes mellitus patients to the Ngronggot Community Health Center and at the village level after the program implementation. The study's conclusions indicate that the WASIAT MANIS counseling program effectively improves treatment adherence and patient awareness of diabetes mellitus management. This program has the potential to become a community-based health promotion strategy that can be implemented sustainably in primary healthcare settings.